2014
DOI: 10.1111/zph.12099
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Salmonella in the Beef Chain in the Republic of Ireland

Abstract: The study investigated the prevalence, concentration and characteristics of Salmonella spp. in the Irish beef chain. A total of 900 samples including bovine hides, carcasses and ground beef were examined for the pathogen over a 2-year study (July 2007-June 2009). Salmonella prevalence was low in all sample types; bovine hide (0.75%, 3 of 400); carcasses (0.25%, 1 of 400); and ground beef (3%, 3 of 100). All positive samples contained the pathogen in low concentrations (<10 CFU per cm(2) or per g). Serovars rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…In Canada, a baseline study conducted between 2006 and 2007 showed that only 0.1% of 1036 beef carcass samples analyzed tested positive for Salmonella (Bohaychuk et al, 2011). In Ireland and Australia, Salmonella prevalence was reported in 0.25% (1/400) and 0.0% (0/1155) of beef carcasses, respectively (Khen et al, 2014;Phillips et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In Canada, a baseline study conducted between 2006 and 2007 showed that only 0.1% of 1036 beef carcass samples analyzed tested positive for Salmonella (Bohaychuk et al, 2011). In Ireland and Australia, Salmonella prevalence was reported in 0.25% (1/400) and 0.0% (0/1155) of beef carcasses, respectively (Khen et al, 2014;Phillips et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…In a study conducted in the US, Salmonella was enumerated in 1520 beef carcass samples using a direct plating method (BrichtaHarhay et al, 2007) and from a total of 757 (49.8%) samples that tested positive for the pathogen, only 144 (19%) had enumerable levels with median and maximum counts of 0.2 and 2.6 Log CFU/100 cm 2 , respectively. More recently, a study conducted in Ireland reported Salmonella isolation from 0.25% of 400 beef carcass samples with levels of b 1 Log CFU/cm 2 (Khen et al, 2014). The Salmonella populations observed on pre chilled beef carcasses during the present investigation (0.3 to 3.4 Log MPN/300 cm 2 ) were higher than those reported in the mentioned studies, and this could be a consequence of the failure to follow good manufacturing practices, the absence of antimicrobial interventions on beef carcasses (pre and postchilling), and the lack of implementation of a food safety system at the abattoirs visited in this study.…”
Section: Resultsmentioning
confidence: 97%
“…This study also revealed high resistance of Salmonella to commonly used antibiotics. Contamination with Salmonella can be further amplified when one considers the possibilities for more contamination as meat passes through the many steps from slaughterhouse to the final consumer [ 29 , 68 ]. Hygiene status must be enhanced to minimize cross contamination of Salmonella from utensils, cutting boards, and knifes as well as from abattoir workers who are involved in the slaughtering process.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies support the role of hide in beef contamination at slaughter, even if a wide variation in prevalence has been reported. It ranged from 36.25% in Venezuela (Narváez-Bravo et al ., 2013), 15.4% in the USA (Bacon et al ., 2002) to 0.75% in Ireland (Khen et al ., 2014). Very high prevalence values were reported by Brichta-Harhay et al .…”
Section: Discussionmentioning
confidence: 99%